Publication of rubber research articles: investigating a discourse event from a macro genre perspective - Charlotte, Veronica (2019)
Producing published research is an endeavour filled with risks, especially from the perspective of novice writers of scientific research articles (hereafter RA). This research project focuses on the environment of scientific research, where there is often little explicit guidance given to early-career academics in language skills surrounding their work. Although the target audience of an RA are researchers in the area, the risks and success involving its publication depend on the relationship between writers and their initial evaluative readers. Journal editors and reviewers represent crucial readers in view of their contribution to enhancing the RA as it evolves from the point of submission towards an unconditional final acceptance. Communication between RA writers and corresponding editors and reviewers reflects a fundamentally interpersonal issue. Lack of experience, awareness and understanding of the entire publication process among novice writers leads to challenges in negotiation and problematic outcomes at the production level. A significant problem for such researchers is the common assumption that a journal research article (RA) is a single, finished text, instead of recognising it as the culmination of a largely dialogic process which itself comprises a macro genre (as per Martin 1992, understood as an interlocking set of genres which operate with an over-riding social purpose).